Psychiatric Morbidities among Patients with Lichen Simplex Chronicus: A Cross-Sectional Study in a Tertiary Care Hospital of South India (GAIMS Journal of Medical Sciences, 2024)
Background: Lichen simplex chronicus (LSC) is one of the chronic and debilitating neuro-dermatological condition which results in lichenified skin plaques. Psychological stress being one of the main reasons behind intense itching which again leads to repeated cycle of itching and temporary relief. Chronic nature of the disease with intense itching is the of the important factor for the development of psychiatric morbidities. Due the scarcity of Indian literature this study was undertaken. Aim is to study the psychiatric morbidities in patients of Lichen simplex chronicus. Materials and methods: This is a cross sectional study conducted in a tertiary care hospital after ethical committee approval.  Total of consenting 150 diagnosed LSC patients were interviewed for psychiatric morbidities using MINI-Plus scale. Results: Major Depressive Disorder was found in 8%, Generalized anxiety disorder (GAD) was present among 13.3.%, social phobia in 15.3% in our study group. One of the females had somatization disorder and other one had obsessive compulsive disorder. Conclusion: Comparatively higher prevalence of psychiatric morbidities was found in our study group which further warrants adequate consultation liaison between dermatology and psychiatry department.